1976
DOI: 10.1007/bf02586286
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of binary systems of saturated fatty acids

Abstract: Data on crystal lattices of t 3 different mixtures of the system palmitic acid:stearic acid (C16/C18) could be obtained by means of X-ray and electron diffraction. The modification occurring in all concentrations was found to be in conformity with the known74-or C-form of the pure components. It is characterized by the fact that, in mixtures with 95-60 mol % stearic acid, the shorter chained palmitic acid molecules may be incorporated in the crystal lattice of pure stearic acid without dimension c of the unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…A similar effect was observed for gelatin‐hydrophobic compounds 17. After re‐heating crystallization seemed to be restricted to quite an extent as concluded from the shift to lower temperatures and reduced peak areas may be due to the restricted mobility of fatty acid chains in the absence of moisture which led to less perfect and stable crystals 35. This could also an indication solid‐solid transition between polymorphic forms of stearic acid induced by palmitic acid in quenched samples 35.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…A similar effect was observed for gelatin‐hydrophobic compounds 17. After re‐heating crystallization seemed to be restricted to quite an extent as concluded from the shift to lower temperatures and reduced peak areas may be due to the restricted mobility of fatty acid chains in the absence of moisture which led to less perfect and stable crystals 35. This could also an indication solid‐solid transition between polymorphic forms of stearic acid induced by palmitic acid in quenched samples 35.…”
Section: Resultssupporting
confidence: 61%
“…After re‐heating crystallization seemed to be restricted to quite an extent as concluded from the shift to lower temperatures and reduced peak areas may be due to the restricted mobility of fatty acid chains in the absence of moisture which led to less perfect and stable crystals 35. This could also an indication solid‐solid transition between polymorphic forms of stearic acid induced by palmitic acid in quenched samples 35. Calorimetric results agreed well with SEM observations and opacity results and confirmed that the dispersed phase in SA/PA‐SPC7 was mainly constituted by the un‐reacted fatty acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of the pure polymorphs of stearic acid exhibit such a strong reflection at d = 4.1 Å, as is observed in case of the blends of this study. Frede et al [16] observed a similar decrease in intensity at 40 Å and increase in intensity at 4.1 Å when they melt blended stearic acid with palmitic acid. However, they did not report the polymorphic transition observed in this study with the blends.…”
Section: © 2004 Iupac Pure and Applied Chemistry 76 1353-1363mentioning
confidence: 70%
“…Long-chain carboxylic acids and esters of fatty acids have already been subjects of thermodynamic and structural analyses under different aspects [10][11][12][13][14][15][16][17][18]. In their solid states unbranched fatty acids from bilayers which are chiefly built up by hydrogen bonds between carboxyl groups [13,19,20].…”
Section: Phase Transitions Of Homologous Fatty Acids and Fatty Acid Mmentioning
confidence: 99%